VIRTUAL SCREENING AND MOLECULAR DOCKING STUDIES OF NOVEL INHIBITORS FOR HIV REVERSE TRANSCRIPTASE - Dr. PVRD PRASADA RAO,; Dr.K.RAMAMOHANA RAO, (International Journal of Pharma and Bio Sciences, 2015)
Human Immunodeficiency Virus is caused by retrovirus in human beings, where the overall immune system fails resulting in opportunistic infections, HIV-1 Reverse Transcriptase (RT) is an important enzyme supporting replication cycle of HIV. Reverse Transcriptase protein an essential focus in the current medications for HIV-1, because of flexible nature of the target proteins, there is a basic need to find novel, powerful medications against HIV. Henceforth, an endeavor has been made to screen ZINC compound Library, Using e-HiTS software in docking process with nevirapine bound HIV-RT, 884 ligands with alike properties were tested for their binding affinity towards targeted enzyme and at last 39 hits were reported as effective inhibitors of HIV-RT Virus.